Immunoassays : development, applications and future trends - Murphy, Caroline; O'Kennedy, Richard (Singapore : Pan Stanford Publishing, 2017)
The concept behind this book is to provide a detailed and practical overview of the development and use of immunoassays in many different areas. Immunoassays are analytical tests that utilise antibodies to measure the amount, activity or identity of an analyte. This book is designed to provide a critical and helpful insight into the subject and to give the user practical information that may be of assistance in assay format selection, antibody generation/selection and choice of appropriate detection strategies. It is comprised of 13 chapters written by highly experienced researchers in the fields of antibody-based research, immunoassay development, assay validation, diagnostics and microfluidics. Beginning with a comprehensive survey of antibodies, immunoassay formats and signalling systems, the book elucidates key topics related to the development of an ideal antibody-based sensor, focuses on the important topic of surface modification, explores key parameters in the immobilisation of antibodies onto solid surfaces, discusses the move to 'lab-on-a-chip'-based devices and investigates the key parameters necessary for their development. Three of the chapters are dedicated to the areas of clinical diagnostics, infectious disease monitoring and food security, where immunoassay-based applications have become highly valuable tools. The future of immunoassays, including next-generation immunoassays, electrochemical-immunoassays and 'lab-on-a-chip'-based systems, is also discussed. The book also covers the use of optical detection systems (with a focus on surface plasmon resonance) in immunoassays, provides a compilation of important, routinely used immunoassay protocols and addresses problems that may be encountered during assay development.--Provided by publisher.
chapter 1 An Overview of Immunoassays / Caroline Murphy Sarah Gilgunn Richard O Kennedy -- chapter 2 Recombinant Antibodies for Diagnostic Applications: Design Considerations and Structural Correlates / Stephen Hearty Richard O Kennedy -- chapter 3 Surfaces and Immobilisation Strategies for Use in Immunoassay Development / Chandra K. Dixit Paul Conroy -- chapter 4 Immunoassay Validation / Paul Leonard -- chapter 5 Lab-on-a-Chip Immunoassay Systems / Barry Byrne Louise M. Barrett -- chapter 6 Clinical Applications of Immunoassays / Karen Lawler Gregor Kijanka -- chapter 7 Immunoassay-Based Detection of Infectious and Parasitic Diseases / Paul J. Conroy -- chapter 8 Detection of Food, Agricultural and Aquatic Contaminants / Marie Le Berre Caroline Viguier Caroline Murphy Niamh Gilmartinb -- chapter 9 Next-Generation Immunoassays / Valerie Fitzgerald Paul Leonard -- chapter 10 Recent Trends and the Future of Electrochemical Immunoassay Systems / Frank Davis Seamus Higson -- chapter 11 Optical Signal Transduction with an Emphasis on the Application of Surface Plasmon Resonance (SPR) in Antibody Characterisation / Caroline Murphy Aoife Crawley Hannah Byrne Kara Moran Jenny Fitzgerald Richard O Kennedy -- chapter 12 Protocols for Key Steps in the Development of an Immunoassay / Caroline Murphy Richard O Kennedy.
Keywords: Immunoassay -- Research; Immunoassay; Immunodiagnosis